Fragmentation fractal of sandstone under acid corrosion and coupled static-dynamic loads - LIU Yong-sheng; LI Jin; ZOU Jia-yu; WU Yun; LU Shao-yong (Functional Materials, 2018)
The analysis results show that the fragment of broken rock is a fractal distribution, and the smaller the impact pressure is, the less specimen fragments is,the lower degree of fragmentation degree is, and the lower fractal dimension is. Research shows that fractal dimension increases with the dynamic compression strength of rock increasing, and the incident energy and the absorb energy increase linear with the fracture fractal dimension increasing. The fragmentation distribution of the specimens becomes more and more uniform with the increasing of the incident energy, and the characteristic scale of rupture decreased gradually.